Unraveling the Role of Ataxin-2 in Metabolism. (April 2017) - Carmo-Silva, Sara; Nobrega, Clevio; Pereira de Almeida, Luís; Cavadas, Claudia
Abstract : Ataxin-2 is a polyglutamine protein implicated in several biological processes such as RNA metabolism and cytoskeleton reorganization. Ataxin-2 is highly expressed in various tissues including the hypothalamus, a brain region that controls food intake and energy balance. Ataxin-2 expression is influenced by nutritional status. Emerging studies discussed here now show that ataxin-2 deficiency correlates with insulin resistance and dyslipidemia, an action mediated via the mTOR pathway, suggesting that ataxin-2 might play key roles in metabolic homeostasis including body weight regulation, insulin sensitivity, and cellular stress responses. In this review we also discuss the relevance of ataxin-2 in the hypothalamic regulation of energy balance, and its potential as a therapeutic target in metabolic disorders such as obesity. Trends: Ataxin-2 is a polyglutamine protein with an important role in RNA metabolism and translation regulation. Emerging data suggest that ataxin-2 might impact on metabolic status and body weight. Several genetic linkage studies have implicated the ATXN2 locus and adjacent regions (12q23–24) in the risk of obesity, hypertension, and cardiovascular disease. Ataxin-2 knockout or depletion in different animal models leads to hyperphagia, obesity, altered lipid metabolism, and insulin resistance. Starvation and mTOR inhibition induce ataxin-2 expression, and ataxin-2 in turn regulates the PI3K/mTOR pathway. Ataxin-2 is present in the hypothalamus, the brain region responsible for control energy and body homeostasis. It could therefore affect physiological functions such as body weight and food intake, circadian rhythm, stress response, and longevity.